2015
DOI: 10.1016/j.micinf.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Dok proteins are recruited to the phagosome and degraded in a GP63-dependent manner during Leishmania major infection

Abstract: Three adaptor molecules of the Dok family, Dok-1, Dok-2 and Dok-3 are expressed in macrophages and are involved in the negative regulation of signaling in response to lipopolysaccharide and various cytokines and growth factors. We investigated the role and the fate of these proteins following infection with Leishmania major promastigotes in macrophages. The protozoan parasite L. major causes cutaneous leishmaniasis and is known for its capacity to alter host-cell signaling and function. Dok-1/Dok-2(-/-) bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…We have previously shown that in IFN-␥-primed macrophages, nitric oxide (NO) and TNF secretion is reduced in DKO cells (45). Thus, Dok-1/2 deficiency could be expected to result in less efficient clearing of the virus during acute infection; however, we found that viral titers in tear films and the kinetics of viral clearance in the eyes were similar in DKO and WT mice.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously shown that in IFN-␥-primed macrophages, nitric oxide (NO) and TNF secretion is reduced in DKO cells (45). Thus, Dok-1/2 deficiency could be expected to result in less efficient clearing of the virus during acute infection; however, we found that viral titers in tear films and the kinetics of viral clearance in the eyes were similar in DKO and WT mice.…”
Section: Discussionmentioning
confidence: 55%
“…The promastigote surface glycolipid lipophosphoglycan (LPG) plays a major role in this inhibition by disrupting phagosomal lipid microdomains [ 8 10 ]. Recent evidence indicates that the glycophosphatidylinositol (GPI)-anchored zinc-dependent metalloprotease GP63 also contributes to the Leishmania- induced phagosomal remodeling [ 7 , 11 ]. Hence, during phagocytosis, GP63 is released from the parasite and rapidly gains access to various intracellular compartments where it cleaves a number of regulators of macrophage function [ 7 , 11 16 ], including regulators of membrane fusion [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that the glycophosphatidylinositol (GPI)-anchored zinc-dependent metalloprotease GP63 also contributes to the Leishmania- induced phagosomal remodeling [ 7 , 11 ]. Hence, during phagocytosis, GP63 is released from the parasite and rapidly gains access to various intracellular compartments where it cleaves a number of regulators of macrophage function [ 7 , 11 16 ], including regulators of membrane fusion [ 7 , 15 ]. One such molecule is the soluble N-ethylmaleimide-sensitive factor-attachment protein receptor (SNARE) Vesicle-associated membrane protein 8 (VAMP8), which we recently showed to control the early recruitment of the NADPH oxidase (NOX2) to phagosomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, liphosphoglycan (LPG), glycosylinositol phospholipids (GIPLs), proteophosphoglycans (PPGs), secreted acid phosphatases (SAPs) and cysteine protease B have been well-explored in this matter [26][27][28][29][30][31][32][33] . The GP63, a zinc-metalloprotease named glycoprotein 63 (GP63), is another critical virulence factor that has been fully explored [34][35][36][37][38] . However, the E-NTPDases (ecto-nucleoside triphosphate diphosphohydrolases), while less-extensively studied, have been demonstrated and believed to be important infectivity and virulence factors [39][40][41][42][43][44][45][46][47][48] .…”
Section: Leishmania Braziliensis Is Responsible For Most Cases Of MLmentioning
confidence: 99%